Identificação e Caracterização do Fungo Fima 665-5, Isolado do Musgo Sanionia Uncinata (hedw.) Loeske, Ilha Rei George, Antártica - Alves, Graciéle Cunha (2014)
Fungi in Antarctica occupy different niches and perform different interactions, but its importance in these niches and interactions are still poorly understood. Interactions between fungi and mosses have been reported to Antarctica an example of these interactions is the presence of fungi forming rings on of carpets Antarctic mosses. These fungi forming rings can cause necrosis and yellow to brown stains on the carpets of mosses. However, due to the complexity of these fungi information about these are fragmented and there is still no complete characterization of these organisms. This study aimed to identify the isolated named FIMA 665-5, found in samples of moss Sanionia uncinata (Hedw.) Loesk. Further, characterize physiological, biochemical and test the presence of pathogenic activity of isolated. The collections of the material for the study were performed at the Brazilian Antarctic Expedition in the austral summer of 2012/2013. Through taxonomic, molecular and phylogenetic methods the isolate was identified belonging to the genus Penicillium Link (1809). For physiological characterization of different culture media (PDA, MEA and Sabouraud) and different temperatures (-6°C, 1°C, 5°C, 10°C, 20°C and 30°C) were tested where the diameter colony was measured with a caliper every 24h, until the growth of a colony reached the edge of the plate. The results were submitted to ANOVA and Tukey test (p <0.05) using the Statistix 8. For the biochemical characterization were performed enzymatic assays with different culture media to verify the production of enzymes such as pectinase, cellulase, protease and amylase at temperatures of 10°C and 30°C. To evaluate the pathogenic activity chemical pathogenicity tests were performed obtained from the isolated extract and by confronting disk diffusion test. Through taxonomic methods, molecular and phylogenetic isolated was identified belonging to the genus Penicillium Link, one psychrotrophs organism, with growth between 1-30°C, with a great mycelial growth at 20°C. The culture medium which has more favorable nutritional conditions for mycelial growth of isolate is PDA medium. Regarding to pathogenicity, the isolate showed ability to inhibit the in vitro growth and cause complete discoloration in the gametophytes of moss Physcomitrium acutifolium Broth.